2023
DOI: 10.1007/s11846-023-00619-y
|View full text |Cite
|
Sign up to set email alerts
|

Linking perceived overqualification to work withdrawal, employee silence, and pro-job unethical behavior in a Chinese context: the mediating roles of shame and anger

Abstract: Using appraisal theories of emotions as the theoretical basis, we delineate how perceived overqualification relates to work withdrawal, employee silence, and pro-job unethical behavior through the mediating effects of discrete emotions (i.e., shame and anger). We suggest that perceived overqualification is positively associated with shame and ultimately work withdrawal and employee silence, and it has a positive effect on pro-job unethical behavior through the mediating role of anger as well as the serial medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 117 publications
0
4
0
Order By: Relevance
“…pay and opportunity to develop oneself) in the workplace (Cheng et al, 2020;Andel et al, 2022). In this case, supervisors who perceive they are overqualified will worry about whether their daily work efforts will be appreciated (Ma et al, 2023) and are likely to face the potential threat that thwarts personal expectations such as status and personal growth (Liu et al, 2023). As supervisors' exploitative behaviors can contribute to their goal-attainment (Garlatti Costa et al, 2022), which can increase their self-worth and recognition from the organization, supervisors may display exploitative behaviors to deal with the threat caused by perceived overqualification.…”
Section: Supervisor Perceived Overqualification and Exploitative Lead...mentioning
confidence: 99%
“…pay and opportunity to develop oneself) in the workplace (Cheng et al, 2020;Andel et al, 2022). In this case, supervisors who perceive they are overqualified will worry about whether their daily work efforts will be appreciated (Ma et al, 2023) and are likely to face the potential threat that thwarts personal expectations such as status and personal growth (Liu et al, 2023). As supervisors' exploitative behaviors can contribute to their goal-attainment (Garlatti Costa et al, 2022), which can increase their self-worth and recognition from the organization, supervisors may display exploitative behaviors to deal with the threat caused by perceived overqualification.…”
Section: Supervisor Perceived Overqualification and Exploitative Lead...mentioning
confidence: 99%
“…Under conditions of a low sense of fairness, employees’ perception of insider status is weakened, and they are more likely to perceive themselves as outsiders of the organization. Existing research has demonstrated that highly perceived overqualified employees engage in more job search behaviors, voluntary turnover, and counterproductive work behaviors [ 75 , 76 , 77 ].…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…(Fine & Edward, 2017;Luksyte et al, 2011). The main reason for counterproductive behavior is that perceived overqualification leads to anger and unhappiness among individuals (Liu et al, 2023). Perceived overqualification also has a negative effect on employee life satisfaction (Gkorezis et al, 2019) In addition, perceived overqualification results in a decline in employee job satisfaction (El-Sawalhy et al, 2022;Johnson et al, 2002;Lobene & Meade, 2013;Maynard et al, 2006;Verhaest & Omey, 2006).…”
Section: Introductionmentioning
confidence: 99%